Materials-based hair follicle engineering: Basic components and recent advances - Yudie Lv; Weili Yang; Perumal Ramesh Kannan; Han Zhang; Rui Zhang; Ruibo Zhao; Xiangdong Kong (Materials Today Bio)
The hair follicle (HF) is a significant skin appendage whose primary function is to produce the hair shaft. HFs are a non-renewable resource; skin damage or follicle closure may lead to permanent hair loss. Advances in biomaterials and biomedical engineering enable the feasibility of manipulating the HF-associated cell function for follicle reconstruction via rational design. The regeneration of bioengineered HF addresses the issue of limited resources and contributes to advancements in research and applications in hair loss treatment, HF development, and drug screening. Based on these requirements, this review summarizes the basic and recent advances in hair follicle regulation, including four components: acquisition of stem cells, signaling pathways, materials, and engineering methods. Recent studies have focused on efficiently combining these components and reproducing functionality, which would boost fabrication in HF rebuilding ex vivo, thereby eliminating the obstacles of transplantation into animals to promote mature development.